Avaliação da inclusão de subproduto agroindustrial na silagem de trigo forrageiro - Oliveira, Sara Naielli de (2019)
In view of the difficulty of obtaining pastures in quantity and quality in times of water scarcity, forage conservation, which stands out for maintaining the nutritional quality allowing ruminants to express their full productive potential. However, in order to avoid deleterious effect, all processes must be careful. The present work aimed to include carbohydrate sources in the green mass to be ensiled using dehydrated jabuticaba bark. The procedures were performed in the laboratory, where the jabuticaba bark was lightly shredded and the particle size reduced to the forced air venting oven until it reached a constant moisture free weight for approximately 72 hours on paper bags with temperature of 45ºC. After drying, it went back to the grinding process, leaving it in millimeter particles. The silos were made of PVC pipe with dimensions of 100 mm diameter x 45 cm high, where the homogenized green mass of wheat with concentrations of 0%, 4%, 9%, 21% and 45% of the jabuticaba were inserted to the silo and compacted. The material and methods start with one of the silos being weighed and their weight noted, then ensiled to the mass and weighed again so that the silo weight is discounted and ascertained to the capacity of material that has been compacted within it, thereby obtaining concentrations in grams of weight of the products that have been incorporated. The homogenization consisted of the splashing of the jabuticaba residue on the forage mass at the time of ensiling, so that they were graduall added to the silo with the aid of wooden sockets to obtain an efficient compaction. After 120 days the silos were opened and samples were taken for the analysis of Dry Matter, Mineral Matter, Neutral Detergent Fiber, Acid Detergent Fiber, Lignin, Crude Protein, pH, Digestibility and Buffer Capacity, where the results will be analyzed. by factorial design.